2004
DOI: 10.1002/chem.200400559
|View full text |Cite
|
Sign up to set email alerts
|

On the Electronic Structure of Ethidium

Abstract: The electronic structure of the common intercalating agent ethidium bromide (3,8-diamino-5-ethyl-6-phenylphenanthridinium bromide) is dominated by an interplay of electron donating and withdrawing effects mediated by its nitrogen atoms. X-ray crystallography, UV/Vis and IR absorption, fluorescence emission, and NMR spectroscopy are used to probe the electronic properties of the phenanthridinium "core" of ethidium as well as its exocyclic amines and 6-phenyl groups. Interestingly, despite its positive charge, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 46 publications
3
35
1
Order By: Relevance
“…This binding would occur through the interaction of partial positive charges caused by localized deficits in p-orbital electrons associated with three of the four nitrogen atoms of PI (Luedtke et al, 2005) coordinating with negatively charged carboxyl and hydroxyl groups on homogalacturonans (HGs), as has been suggested in Oedogonium bharuchae (Estevez et al, 2008).Our findings indicate that both hypotheses are satisfied. Notably, oscillatory changes in apical PI fluorescence occur and are observed to anticipate oscillations in growth rate in Arabidopsis (Arabidopsis thaliana) root hairs and Arabidopsis pollen tubes.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…This binding would occur through the interaction of partial positive charges caused by localized deficits in p-orbital electrons associated with three of the four nitrogen atoms of PI (Luedtke et al, 2005) coordinating with negatively charged carboxyl and hydroxyl groups on homogalacturonans (HGs), as has been suggested in Oedogonium bharuchae (Estevez et al, 2008).Our findings indicate that both hypotheses are satisfied. Notably, oscillatory changes in apical PI fluorescence occur and are observed to anticipate oscillations in growth rate in Arabidopsis (Arabidopsis thaliana) root hairs and Arabidopsis pollen tubes.…”
supporting
confidence: 59%
“…While there are no published studies on the electronic structure of PI, we can look to investigations of ethidium bromide, which contains an identical phenanthridine core. X-ray crystallography, UV/ visible and IR absorption, fluorescence emission, and NMR spectroscopy studies (Luedtke et al, 2005) show that the carbon and hydrogen atoms of the phenanthridium structure have relatively high electron densities, while nitrogen atoms are electron deficient, resulting in three positively charged regions in the molecule spaced 6 to 7 Å apart. We reasoned that if PI were interacting with the negative carboxyl groups in HGs, as our pollen tube and root hair data suggested (McKenna et al, 2009) .…”
Section: Pi Fluorescence Oscillations Precede Growth Rate Oscillationmentioning
confidence: 99%
“…[21] NMR spectroscopy studies by Leupin et al using 3-and 8-deaminoethidium revealed that the removal of the 8-amino group had little effect on the binding to DNA, whereas the removal of the 3-amino group greatly affected the intercalation. [25] The most recent study by Tor and co-workers showed the influence of such modifications on the electronic structure of E. [26] This study included 5-ethyl-6-phenylphenanthridinium (3,8-dideaminoethidium, 1) that was also previously described by others. [24,[27][28][29] On the other hand, several theoretical chemical calculations have shown that the quaternization at position 5 adds significantly to the intercalation properties of phenanthridines.…”
Section: Introductionmentioning
confidence: 99%
“…4,9-diazapyrene) were often applied for an "aryl" component due to characteristic structural features like a permanent or pH induced positive charge, high polarizability, high electron affinity and highly polar amino groups. 4 In addition, it was shown that the chemical modulation of the phenanthridine exocyclic amines is a profitable option to tune the nucleic acid recognition properties of phenanthridinium dyes. 5 A lot of experimental data on ethidium derivatives have been collected over the last three decades 6 including a design of two-colour RNA intercalating probe for cell imaging applications 7 , photoaffinity labelling 8 and antibiotic as well as antitumor activity.…”
Section: Introductionmentioning
confidence: 99%